Multiple taxes levied on deceased estates:A comparison of the determination of the value and the taxation of limited interests for estate duty,capital gains tax and value-added tax - Stemmet, Vicki (Department of Finance and Tax, 2019)
South Africa has one of the highest wealth inequality rates in the world, and there is a dire need for practical methods of redistribution of wealth in South Africa (SA). For this reason, the need for wealth tax in SA is undeniable however the multiple taxes imposed on deceased estates have generated discussions, with many being of the opinion that the taxes imposed on deceased estates are excessive. The main objective of this research is to discuss the multiple taxes levied on certain limited interests in property on death. The imposition of estate duty (ED), capital gains tax (CGT) and value-added tax (VAT) on usufructuary and fiduciary interests in deceased estates were examined. The valuation methods and taxation of these limited interests for the aforementioned taxes were compared to determine if they are stream-lined and if any relief is provided between taxes. It was found that valuation methods and taxation methods are not stream-lined and it appears that no interplay exists between taxes. The substantial differences in valuation and taxation methods between taxes results in the same asset being taxed at different values for each tax. This places a heavy administrative burden on the executors of deceased estates and goes against the characteristics of an efficient tax system which should be fair, simple and easy to administer. Due to the complexities involved in the different tax computations of these rights, it was not possible to provide a conclusive answer regarding whether or not taxes imposed on deceased estates are fair or excessive. In conclusion, however, recommendations have been made to align deductions and valuation methods across taxes in order to bring about transparency which would enable the determination of whether or not the tax burden is excessive and identification of any weaknesses in the tax systems. The alignment could ultimately result in a more efficient tax system, and could address and resolve the concerns regarding the levying of multiple taxes on the same asset in deceased estates.